Study of Building Mass Forms in Jardin Cihampelas Apartment - Andiyan Andiyan; Wima Alkad Albadira (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2021)
Cihampelas Street Bandung is one of the main tourist destinations in Bandung; besides that, Cihampelas is also a residential area with a high population density. Jalan Cihampelas has many residential places, one of which is the Jardin Cihampelas Apartment. The Jardin Cihampelas Apartment is a building consisting of 4 building towers, namely towers A, B, C, and D. Each tower has 23 floors, and a U shape, Tower A - B and C - D are located close to each other on the inside of the "U" shaped mass surrounding the swimming pool. The approach used is geometry, and basic shapes, geometry, and basic shapes show that architecture is an expression of humans and is a basic principle always present from a work of architecture. This research aims to study the relationship between geometric shapes that affect the Jardin Cihampelas apartment building mass. The method used is a descriptive qualitative method using field surveys; the research study is the shape of the building mass in geometric shapes. The research variables discussed include basic form, unity, proportion, balance, rhythm, and emphasis. This research is expected to get useful results from studying the mass shape of the building in the Jardin Cihampelas apartment with the residential typology of tall buildings with geometric shapes in the processing of space in structures.